Optimization of CRISPR-Cas9 system in Eustoma grandiflorum - Xueqi Li; Fanqi Bu; Lishan Wang; Cholmin Kim; Wanjie Xue; Man Zhang; Saneyuki Kawabata; Qingzhu Zhang; Yuhua Li; Yang Zhang (iScience, 2024)
Summary: The optimization of the CRISPR-Cas9 system for enhancing editing efficiency holds significant value in scientific research. In this study, we optimized single guide RNA and Cas9 promoters of the CRISPR-Cas9 vector and established an efficient protoplast isolation and transient transformation system in Eustoma grandiflorum, and we successfully applied the modified CRISPR-Cas9 system to detect editing efficiency of the EgPDS gene. The activity of the EgU6-2 promoter in E. grandiflorum protoplasts was approximately three times higher than that of the GmU6 promoter. This promoter, along with the EgUBQ10 promoter, was applied in the CRISPR-Cas9 cassette, the modified CRISPR-Cas9 vectors that pEgU6-2::sgRNA-2/pEgUBQ10::Cas9-2 editing efficiency was 37.7%, which was 30.3% higher than that of the control, and the types of mutation are base substitutions, small fragment deletions and insertions. Finally we obtained an efficient gene editing vector for E. grandiflorum. This project provides an important technical platform for the study of gene function in E. grandiflorum.